Maternal hemodynamics, arterial stiffness and elastic aortic properties in twin pregnancy. (28th December 2020) - Orabona, Rossana; Sciatti, Edoardo; Vizzardi, Enrico; Bonadei, Ivano; Metra, Marco; Sartori, Enrico; Frusca, Tiziana; Pinna, Antonio; Bellocco, Rino; Prefumo, Federico
Abstract: Objective : There is scant information about maternal cardiovascular hemodynamic change during twin pregnancies. Aim of the study is to investigate longitudinal changes in maternal arterial stiffness, elastic aortic properties and ventricular-arterial coupling (VAC) in uncomplicated twin pregnancies compared to singleton ones. Approach : In this prospective longitudinal study, we performed applanation tonometry and transthoracic echocardiography in the first (T1; 10–15 weeks' gestation (w)), second (T2; 19–26 w) and third trimesters (T3; 30–38 w) in women with uncomplicated twin pregnancies, both monochorionic and dichorionic. Heart-rate-corrected augmentation index (AIx@75) was studied as indicator of arterial stiffness. Aortic diameters and elastic properties were calculated. VAC was defined as the ratio between aortic elastance (Ea) and left ventricular end-systolic elastance (Ees). Finally, stroke volume (SV), cardiac output (CO) and total vascular resistance (TVR) were evaluated. The findings were compared to those of women with uncomplicated singleton pregnancies. Main results : Thirty women with twin gestations (11 monochorionic) and 30 singleton controls were obtained for analysis. Blood pressure and TVR significantly decreased from T1 to T2 and then rose in T3, with higher values in twins than in singletons. AIx@75 showed the same trend in both groups with lower values at T2 in twins. SV and CO linearly increased throughout gestation with no significant intergroup difference. Aortic diameters and elastic properties remained stable throughout gestation, with no significant intergroup differences. Both Ea and Ees were greater (i.e. worse) in twins than in singletons at T1 and T3, showing a significant linear trend towards reduction in the two groups, meaning lower vascular and ventricular loads. Using longitudinal analysis blood pressure, TVR, Ea and Ees depended from both multiple gestation and gestational age. Significance : In twins, maternal hemodynamics does not seem to undergo more significant changes than in singletons being characterized by higher blood pressures and TVR with no differences in CO, SV, aortic dimensions and elastic properties. Despite VAC is maintained within its normal range, total vascular load (i.e., Ea) resulted higher in twin than singleton pregnancies throughout gestation. It is conceivable that these findings may represent one of the underlying cause for the increased risk of adverse obstetric outcomes described in multiple gestations.